Minimising efficiency roll-off in high-brightness perovskite light-emitting diodes - Wei Zou (Nature Portfolio, 2018)
Large drop in efficiency at high brightness has been holding back the development of various light-emitting diodes including halide perovskite. Here Zou et al. achieve high quantum efficiency of 10% under a high current density of 500 mA cm−2 in perovskite-based diodes by reducing luminescence quenching.